The professional profile of the huanuqueño economist in pos-Covid times - Tello-Cornejo, Janeth L. (2025)
The purpose of this study was to identify, describe, and explain the necessary professional competencies that Huánuco economists must develop and possess in a complex post-pandemic scenario. The research was framed within a quantitative approach methodology, using a non-experimental design, based on the observation of the profile of the Huánuco economist in the post-COVID period, of an applied type. The study worked with 203 economists, divided into 102 professionals and 101 business owners, to whom a questionnaire was administered as part of the study's data collection instrument. The most notable results were that the competencies considered very important by economists are critical thinking (56.1%), ethical decision-making (57.7%), data and statistical analysis (40.9%), and communication skills (38.7%). Furthermore, 33.3% of economists perceive that challenges outweighed opportunities after the pandemic, followed by those who believe there is a balance between the two (29.4%). Regarding the dynamics of the post-pandemic labor market, 42.9% considered that there were no significant changes, while 25.6% perceived improvements. It is concluded that the profile of the professional economist should be based on both technical and soft skills, underscoring that the dynamics of the labor market are complex, with specific and well-defined professional demand. Keywords: life skills, economist, professional training, profession.